Merkel cell polyomavirus and its etiological relationship with skin tumors - Thiago Rubim Bellott; Flávio Barbosa Luz; Anna Karoline Fausto da Silva; Rafael Brandão Varella; Mayra Carrijo Rochael; Luciana Pantaleão (Anais Brasileiros de Dermatologia, 2023)
Abstract Viruses have been frequently identified in several human neoplasms, but the etiological role of these viruses in some tumors is still a matter of controversy. Polyomaviruses stand out among the main viruses with oncogenic capacity, specifically the Merkel cell polyomavirus (MCPyV). Recent revisions in the taxonomy of polyomaviruses have divided the Polyomaviridae family into six genera, including 117 species, with a total of 14 currently known human-infecting species. Although the oncogenicity of polyomaviruses has been widely reported in the literature since 1950, the first description of a polyomavirus as an etiological agent of a neoplasm in humans was made only in 2008 with the description of MCPyV, present in approximately 80% of cases of Merkel cell carcinoma (MCC), with the integration of its genome to that of the tumor cells and tumor-specific mutations, and it is considered the etiological agent of this neoplasm since then. MCPyV has also been detected in keratinocyte carcinomas, such as basal cell carcinoma and squamous cell carcinoma of the skin in individuals with and without immunosuppression. Data on the occurrence of oncogenic viruses potentially involved in oncogenesis, which cause persistence and tissue injury, related to the Merkel cell polyomavirus are still scarce, and the hypothesis that the Merkel cell polyomavirus may play a relevant role in the genesis of other cutaneous carcinomas in addition to MCC remains debatable. Therefore, the present study proposes to explore the current knowledge about the presence of MCPyV in keratinocyte carcinomas.